Hubungan Pengetahuan dan Kebiasaan Sarapan dengan Kejadian Anemia Pada Remaja Putri - Meikawati, Pedvin Ratna; Utami, Suci; Haq, Ismi Arianal (JURNAL KESEHATAN TERAPAN, 2025)
Anemia is a condition in which the hemoglobin (Hb) or number of red blood cells is below normal and insufficient to meet a person's physiological needs. Breakfast contributes around 25% of a day's nutritional intake. A person's knowledge can influence the number of cases of anemia in teenagers. Lack of knowledge about the signs, effects and prevention of anemia causes young women to consume foods that do not contain much iron. The aim of this study was to determine the relationship between knowledge and breakfast habits and the incidence of anemia in adolescent girls. This research is a quantitative research with a cross sectional approach. The population in this study was 40 teenagers and the sample in this study was 30 respondents, with the criteria for students being female students aged 12-14 years. The technique used in sampling is purposive sampling technique. Data collection uses a questionnaire. The results of the study showed that there was no relationship between knowledge and the incidence of anemia in young women with a value of p= 0.260 (p> 0.05). Meanwhile, the relationship between breakfast habits and the incidence of anemia in adolescent girls is known to be p = 0.631 > a = 0.05, so it can be concluded that there is no significant relationship between breakfast habits and the incidence of anemia in adolescent girls. There is no relationship between knowledge and breakfast habits and the incidence of anemia in young women at the Al-Falah Sofwaniyah Islamic Boarding School.